Time and age dependent regulation of neuroinflammation in a rat model of mesial temporal lobe epilepsy: Correlation with human data - Erisken, Sinem; Nune, George; Chung, Hyokwon; Kang, Joon Won; Koh, Sookyong (Frontiers in Cell and Developmental Biology, 2022)
Acute brain insults trigger diverse cellular and signaling responses and often precipitate epilepsy. The molecular and signaling events relevant to the emergence of epileptic brain, however, remain poorly understood. These multiplex structural and functional alterations tend to be opposing - some homeostatic and reparative while others disruptive; some associated with growth and proliferation while others, with cell death. To differentiate pathologic from protective consequences, we compared gene expression changes hours and days following kainic acid (KA)-induced status epilepticus (SE) in postnatal day (P) 30 and P 15 rats by capitalizing on age-dependent responses to KA-SE: P30 animals develop epilepsy while P15 animals show no cell death and no spontaneous recurrent seizures. Higher and sustained proinflammatory genes were expressed in P30. The inflammatory response was driven by the cytokines IL-1β, IL-6, and IL-18 in the acute period up to 72 hours and by IL-18 through 10-days. Also upregulated was a panoply of other inflammatory genes including chemokines, glia markers and adhesion molecules. Genes associated with the mitogen activated protein kinase (MAPK) pathways comprised the largest functional group. We analyzed genes belonging to 13 “Classical MAPK” ERK pathways, as well as stress activated protein kinases (SAPKs) p38 and JNK. Genes belonging to the Classical MAPK pathways were mostly transiently activated while genes in the SAPK pathways had divergent time courses of expression, showing sustained activation only in P30. In addition, P30 animals showed marked increases in positive regulators of transcription, of signaling pathways and of MAPKKK cascades. In the brain, many immune molecules have additional roles in synaptic plasticity and the promotion of neurite outgrowth. We propose that persistent changes in inflammatory gene expression after SE leads not only to structural damage but also to aberrant synaptogenesis that may lead to epileptogenesis. Furthermore, the sustained pattern of inflammatory genes upregulated in epileptic mature brain was distinct from transient expression in immature brain resistant to cell death and neuropathologic changes. Our data suggest that the epileptogenic process may be a result of failed cellular signaling mechanisms, where insults overwhelm the system beyond a homeostatic threshold.